2017
DOI: 10.1017/jmo.2017.2
|View full text |Cite
|
Sign up to set email alerts
|

A within-country study of leadership perceptions and outcomes across native and immigrant employees: Questioning the universality of transformational leadership

Abstract: This study investigates the universality of transformational leadership with respect to employee perceptions and three outcomes: job satisfaction, self-rated health, and well-being. We do so among employees of different national and cultural backgrounds, yet within a shared national and sectorial setting. Our study has a repeated measures design based on survey data from 2,947 employees (2,836 natives Danes and 111 immigrants) in the Danish elder care sector. While we find no difference between native Danes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 76 publications
(85 reference statements)
1
20
0
Order By: Relevance
“…This study contributes to the literature in more than one way. Despite the fact that there are calls in the extant literature for investigating explanatory mechanisms of the relationship between transformational leadership and OCB (Ng, 2017;Wang et al, 2011;Holten et al, 2018;Pan and Lin, 2015;Patiar and Wang, 2016), very little has been researched so far. Therefore, the present study fills the gap in the literature that mediating mechanisms in the relationship between transformational leadership and OCB are missing a theoretical grounding (Ng, 2017;Van Knippenberg and Sitkin, 2013).…”
Section: Implications For Theory and Practicementioning
confidence: 99%
“…This study contributes to the literature in more than one way. Despite the fact that there are calls in the extant literature for investigating explanatory mechanisms of the relationship between transformational leadership and OCB (Ng, 2017;Wang et al, 2011;Holten et al, 2018;Pan and Lin, 2015;Patiar and Wang, 2016), very little has been researched so far. Therefore, the present study fills the gap in the literature that mediating mechanisms in the relationship between transformational leadership and OCB are missing a theoretical grounding (Ng, 2017;Van Knippenberg and Sitkin, 2013).…”
Section: Implications For Theory and Practicementioning
confidence: 99%
“…Nonetheless, workplace green behavior research has tended to examine leadership styles such as ethical leadership (Zhang et al, 2016) or transformational leadership (Kura, 2016;Robertson and Barling, 2013). These leadership styles may, however, be universal (Holten et al, 2018). Specific leadership style can influence specific self-identity (Chen et al, 2015), thereby influencing their specific intention and behavior (Conchie et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There is a long-standing debate in the literature between competing propositions regarding the universalistic vs culture-contingent elements of effective leadership (e.g. House et al , 1997; Hamlin, 2004; House et al , 2004; Holten et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, while some leadership behaviors are culturally sensitive, other attributes seem to be universally accepted characteristics that identify good leaders worldwide, such as value-based and charismatic/transformational leadership (Den Hartog et al , 1999; House et al , 2004; Dorfman et al , 2012) – despite some evidence on the contrary reported by Holten et al (2018). Meanwhile, characteristics such as being solitary, non-cooperative, ruthless, non-explicit, irritable and dictatorial are considered universally not acceptable in a leader (Den Hartog et al , 1999).…”
Section: Introductionmentioning
confidence: 99%